Associations Between Mother–Child Communication Apprehension, and Young Adult Resilience, Depressive Symptoms, and Self-Esteem. Issue 3 (June 2021) - Curran, Timothy; Seiter, John; Guan, Mengfei; White, Taylor
This study tested associations between mother–child communication apprehension, adult child communication apprehension, and adult child resilience, self-esteem, and depressive symptoms. Data were collected from 154 mother–child dyads ( N  =   308) who completed measures of communication apprehension, depressive symptoms, resilience, and self-esteem. Results showed that mother communication apprehension positively predicted adult child communication apprehension. Moreover, adult child communication apprehension predicted lower levels of resilience and self-esteem, and higher levels of depressive symptoms. Mother communication apprehension indirectly predicted all three psychological outcomes for adult children through adult children's communication apprehension. We discuss the potential implications for communication apprehension and social skill training that could help families improve psychological problems.